Legal Analysis of the Position and Impact of Misuse of E-Stamps in Electronic Documents: A Civil Law Perspective - Wildan Asyraf, Andi Muhammad; Arsy, Muhammad; Adha Hamza, Yuli (ADVANCED PRIVATE LEGAL INSIGHTS, 2025)
This study aims to analyze the legal position of e-stamp duty in electronic documents based on Indonesian laws and regulations, especially Law No. 10 of 2020 on Stamp Duty. Furthermore, it seeks to examine the legal impact of e-stamp duty misuse from a civil law perspective. This study employs a normative juridical research method, which involves examining legal theories, comparative laws, structure, and general explanations. The findings indicate that e-stamp duty holds a strong legal position as a validation tool for electronic documents under Law No. 10 of 2020 and Article 5 of the ITE Law. However, misuse of e-stamp duty, such as forgery or unauthorized use, can weaken document validity, making them inadmissible as evidence under Article 1869 of the Civil Code. Additionally, misuse undermines public trust in digital administration systems. This study recommends strengthening regulations related to e-stamp duty, including better legal protection for electronic documents, enhanced security systems to detect fraud, and increased public awareness regarding the importance of document validation using e-stamp duty. Law enforcement authorities are encouraged to take firmer action against misuse cases to deter fraud and enhance public confidence in Indonesia's digital administration system.